Hydrothermal liquefaction of municipal wastewater sludge and nutrient recovery from the aqueous phase. Issue 5 (28th May 2022) - Kumar, Vinod; Jaiswal, Krishna Kumar; Vlaskin, Mikhail S.; Nanda, Manisha; Tripathi, M. K.; Gururani, Prateek; Kumar, Sanjay; Joshi, Harish Chandra
Abstract: The hydrothermal liquefaction of municipal sludge was investigated under isothermal conditions (255 °C, 45 min) with TiO2 as a catalyst. In this study, we used two separation methods (an organic solvent-assisted extraction method and the Soxhlet extraction method) for the production of bio-crude oil. The maximum yield of bio-crude oil was 20.7 wt. % reported with the Soxhlet extraction method. The aqueous phase was examined for TN, TP, COD, and TOC to determine the suitability of this phase for microalgae cultivation. Four strains of oleaginous microalgae were cultivated in the aqueous phase. The results show that the growth of microalgae in the aqueous phase was lower compared to the control medium; this may be due to the high COD value. Microalgae and yeast co-cultivation increases biomass and lipid productivity using nutrients in the aqueous phase.